(untitled) (Scientific journal of the Fergana State University, 2023)
The article reveals the facts of using the" mobilization " of the Tatars to strengthen the Soviet power in Turkestan, who shared a common language, religion and culture with the peoples of the region. The article also States that the Tatars were initially sent to strengthen the Soviet power, but later, in 1921-1923, due to the famine in the Volga region, they invited family members, relatives and even colleagues to Turkestan under various pretexts. It was analyzed that the Center effectively used Tatars in " personnel support” and in the management system and military-political relations to strengthen the Soviet power.